The Role of Evaluation in Gifted Program Development: Coordinators' Portraits of Progress. Issue 4 (October 2019) - VanTassel-Baska, Joyce
This article presents a description of the potential impacts from six different school-based evaluations, based on the perceptions of program coordinators and evaluators 1 to 3 years after the evaluation was conducted. It shares data on what recommendations of the evaluation were implemented and the rationale behind these decisions. Coordinators also commented on the perceived value and benefit of having the evaluation conducted and provided thoughts about having an evaluation conducted in the future. The article concludes with a set of lessons learned from the evaluation experience.